Characteristics and Genetic Mechanisms of Normal-Pressure Fractured Shale Reservoirs: A Case Study From the Wufeng–Longmaxi Formation in Southeastern Chongqing, China - Wang, Jinxi; Tan, Xianfeng; Wang, Jia; Zhang, Hualian; Zhang, Ye; Guo, Dongxin; Wang, Xiaofeng; Lei, Zhian; Zeng, Chunlin; Yao, Guanghua (Frontiers in Earth Science, 2021)
Exploring the changes in the physical properties of shale reservoirs under a normal pressure accumulation environment is of great significance to shale gas exploration. X-ray powder diffraction, nitrogen adsorption, and scanning electron microscopy were used to study the well core samples of the Wufeng–Longmaxi Formation in southeastern Chongqing, China. The research results indicate that there are structural fractures in southeastern Chongqing, which are the main storage space for shale gas. High-quality shale reservoirs are located in the lower part of the Wufeng–Longmaxi Formation; these reservoirs have low porosity and low permeability, and structural fractures can improve their permeability to a certain extent. The main factors that control the characteristics of the reservoir include the depositional environment, mineral composition, organic carbon content, and tectonic movement. The deep-water anoxic sedimentary environment is conducive to the complete preservation of organic matter and the sedimentation of biogenic siliceous minerals, which has an important effect on improving the porosity of organic matter and the brittleness of rocks. The high content of quartz and clay minerals can improve rock compression resistance and brittleness as well as the interlayer structure of clay minerals. Organic carbon content, specific surface area, pore volume, and fracture development all have direct contributions to shale gas exploration. Although tectonic movement improves reservoir permeability, it destroys the original overpressure accumulation conditions.